The Chibok girls the Boko Haram kidnappings and Islamic militancy in Nigeria - Habila, Helon 1967- (Columbia Global Reports, 2016)
"Acclaimed novelist Helon Habila, who grew up in northern Nigeria, returned to Chibok and gained intimate access to the families of the kidnapped to offer a devastating account of a tragedy that stunned the world. With compassion and a deep understanding of the historical context, Habila tells the stories of the girls and the anguish of their parents; chronicles the rise of Boko Haram and the Nigerian government's inept response; and captures the indifference of the media and the international community whose attention has long moved on. Employing a fiction writer
Keywords: Boko Haram; Frau; Terrorismus; Mädchen; Entführung; Afrika; Nigeria; Women / Abuse of / Nigeria; Islamic fundamentalism / Nigeria; Terrorism / Nigeria; Islamic fundamentalism; Terrorism; Women / Abuse of; HISTORY / Africa / Central